The effect of Abelmoschus esculentus L. (Okra) extract supplementation on dietary intake, appetite, anthropometric measures, and body composition in patients with diabetic nephropathy - Omid Nikpayam; Ehsan Safaei; Nazgol Bahreyni; Vahideh Sadra; Maryam Saghafi-Asl; Laleh Fakhr (Tabriz University of Medical Sciences, 2022)
Background: Diabetes is a risk factor for chronic kidney disease because it induces nephropathy. Okra is a rich source of antioxidants, vitamins, minerals, and fibers, of which favorable effects in diabetes have been reported in many animal studies. The present trial aimed to investigate the effect of dried okra extract (DOE) supplementation on anthropometric measures, body composition, appetite, and dietary intake in diabetic nephropathy (DN) patients. Methods: In this triple-blind placebo-controlled randomized clinical trial, 64 DN patients were randomly allocated to receive a 125-mg capsule of DOE (n=32) or placebo (n=32) for 10 weeks. At baseline and endpoint of the trial, anthropometric variables, body composition indices, dietary intake, and appetite scores were evaluated. Results: The results showed that energy (P=0.047, CI: -425.87, -3.25, ES: 0.539) and carbohydrate (P=0.038, CI: -85.64, -2.53, ES: 0.555) intake as well as desire to eat salty food (P=0.023) were reduced in DOE group at the endpoint, compared to the baseline values. However, anthropometric measures, body composition, and appetite score were not significantly different between the two study groups. Conclusion: In conclusion, the present clinical trial showed that DOE could significantly decrease energy intake and carbohydrate consumption in the DN patients. Further clinical trials are needed to determine the effects of this supplement.